A rapid method to measure melatonin in biological fluids (milk and serum) with liquid chromatography-tandem mass spectrometry. (15th March 2023) - Yao, Songyang; Liu, Xuening; Fu, Yao; Guan, Shengyu; Liu, Yunjie; Yan, Laiqing; He, Pingli; Liu, Guoshi
Highlights: A modified method to detect melatonin in serum and milk with liquid chromatography tandem mass spectrometry (LC-MS/MS). Comparisons of different pre-treatment procedures on melatonin extraction from milk. Cold methanol is used to improve melatonin extraction efficiency. Abstract: Since the global demanding of natural melatonin-enriched milk has been significantly increased in the populations of children and elder, the accurate and quick melatonin detection from milk is urgently required. Thus, the regular methods no longer satisfy this requirement. In the current study, we reported a novel method to extract melatonin from milk for liquid chromatography-tandem mass spectrometry melatonin detection. This novel method was to use cold methanol (-20℃) to precipitate proteins and fat in milk with one step to extract melatonin. Compared to the regular methods, it was devoid of procedures of sample drying, solid phase extraction and sample reconstitution. It could short the extraction time from the regularly 150 min to 60 min/per 24 milk samples. We believe that this novel method provides a possibility to detect large scale of milk samples in relatively short time with more efficiency and less cost compared to the regular method.